Buying And Selling Online (Shopee) Among Students - Saragih, Tiara Hasanah Putri; Nasution, Muhammad Irwan Padli; Sundari , Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
Research discusses "Buying and Selling Online (Shopee) Among Students". The objectives of this study are: 1) To describe the importance of using shopee among students, 2) To find out why students prefer shopping online rather than in person. This research aims to find out and understand the importance of using the shopee and why they prefer to shop online, especially students. This study used the literature method, which was compiled on the basis of 1) selecting library sources, 2) tracing library sources, 3) reading library sources, 4) keeping records, 5) presenting a literature review. The results of the study show the following: 1) The importance of using shopee among students is because it is easier, economical, time efficient and so on and goods are delivered directly to the house, 2) The reason students choose to shop online rather than in person is because almost the majority of students use shopee in shopping although there are also some people who shop in person on the grounds that traditional shopping is more secure than online shopping, and it turns out that students prefer to shop online.